Electrochemical and material characteristics of Ba0.5Sr0.5Co0.8Fe0.2O3−δ-Sm0.2Ce0.8O1.9 carbonate perovskite cathode composite for low-temperature solid oxide fuel cell. Issue 23 (1st December 2022) - Tan, K.H.; Rahman, H.A.; Azami, M.S.; Yusop, U.A.; Baharuddin, N.A.; Ma'arof, M.I. Nor
Abstract: This paper presents the development of a new composite cathode Ba0.5 Sr0.5 Co0.8 Fe0.2 O3−δ -Sm0.2 Ce0.8 O1.9 carbonate (BSCF-SDCC). The BSCF-SDCC (50 wt% BDCF: 50 wt% SDCC) composite cathode was developed by low-speed ball milling in ethanol. The composite cathode is prepared in powder and pellet form, followed by calcination at 600 °C. The BSCF-SDCC composite cathode is examined by microstructural analysis, phase analysis, chemical bonding, thermal expansion coefficient (TEC), thermogravimetric analysis (TGA), and electrochemical impedance spectroscopy. X-ray diffraction proves the vigorous reaction between BSCF and SDCC powder after calcination. The carbonate bond in BSCF-SDCC was assessed by Fourier transform infrared spectroscopy (FTIR). TECs of the BSCF-SDCC cathode and SDCC matched each other. In TGA, BaCO3 weight gain is observed at 400 °C-650 °C for BSCF-SDCC powder without calcination. In general, BSCF-SDCC powder is not encouraged for calcination, but its pellet form is suitable. Electrochemical performance is tested from 400 °C to 600 °C. BSCF-SDCC after sintering achieves the lowest polarization resistance of 0.45 Ω, lowest area specific resistance of 0.29 Ωcm 2, and highest conductivity of 149.0 Scm -1 at 600 °C. The conductivity is nearly 122% higher than BSCF, which only has a conductivity of 67 Scm -1 . This is due to the existing carbonate layer which reduce the polarization loss and facilities the ions' conduction, thus electric conductivity is increased. The findings reveal a promising characteristic of the BSCF-SDCC composite for low-temperature solid oxide fuel cell cathode application.